Co-assembled Supramolecular Nanofibers With Tunable Surface Properties for Efficient Vaccine Delivery - Wang, Zhongyan; Ren, Chunhua; Shang, Yuna; Yang, Cuihong; Guo, Qingxiang; Chu, Liping; Liu, Jianfeng (Frontiers in Chemistry, 2020)
The utilization of nanotechnology to deliver vaccines and modulate immunity has shown great potential. Supramolecular hydrogels based on peptides as a novel vaccine adjuvant have been found to effectively improve the immune response and tumor curative effect. In this study, we designed a set of enzyme-responsive self-assembling peptide precursors (Fbp-GDFDFDYD(E, S or K)-ss-ERGD), which can be reduced by glutathione (GSH) into Fbp-GDFDFDYD(E, S or K) for formation of hydrogel with different surface properties (E-gel, S-gel and K-gel, respectively). In the same way, precursor solutions mixed with antigens can be used to prepare co-assembled hydrogel vaccines (E-vac, S-vac and K-vac, respectively). Through observation of the nanostructure of all gels, we found that the co-assembled hydrogels, especially K-vac, had denser and unified nanofiber networks compared to antigen-free hydrogels, which was very beneficial for antigen storage and vaccine delivery. Peptides in three co-assembled hydrogels also adopted similar β-sheet secondary structure. However, the mechanical properties of co-assembled hydrogel vaccines were obviously different. For medium E-vac, S-vac had a reduced mechanical property, K-vac had a higher. In vivo experiments, co-assembled hydrogel vaccines, especially K-vac, also promoted antibody production and anti-tumor immune responses. Our results demonstrated that co-assembled hydrogels are effective vaccine delivery systems for antibody production and therapeutic tumor vaccine development, and different surface properties had discernable effects on biofunction of supramolecular nanomaterials.